Impulsivity Mediates the Link between Childhood Sexual Abuse and Juvenile Incarceration among Low-Income African American Women. Issue 3 (16th March 2021) - Harris, Catherine E.; Carter, Sierra; Powers, Abigail; Bradley, Bekh
ABSTRACT: A history of childhood trauma has been found to have a robust influence on juvenile delinquency, and evidence suggests that childhood sexual abuse is particularly common among female youth involved in the juvenile justice system. The current study sought to investigate impulsivity as a potential mediator of the relationship between childhood sexual abuse (CSA) and juvenile incarceration amongst a community sample of low-income, urban, African American adult women. Although impulsivity has been studied among justice-involved youth, few studies have examined the influence of impulsivity within the relationship between CSA and juvenile incarceration and no known studies have explored their relationship in community populations of African American women with histories of juvenile incarceration. Results revealed that impulsivity mediated the relationship between CSA and previous juvenile incarceration. As an exploratory analysis, overall emotion dysregulation as well as other facets of emotion dysregulation did not serve as significant mediators in this relationship. These findings suggest that difficulties in impulse control may be one mechanism through which childhood sexual abuse increases risk for juvenile justice system involvement among African American women.